A Note on "The Ordering of Portfolios in Terms of Mean and Variance" - Klevorick, Alvin K. (Review of Economic Studies, 1973)
Journal Article A Note on “The Ordering of Portfolios in Terms of Mean and Variance” Get access Alvin K. Klevorick Alvin K. Klevorick Cowles Foundation, Yale University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 40, Issue 2, April 1973, Pages 293–296, https://doi.org/10.2307/2296655 Published: 01 April 1973